Coping with Everyday Life for Home-Dwelling Persons with Dementia: A Qualitative Study - Moe,Aud; Alnes,Rigmor Einang; Nordtug,Bente; Blindheim,Kari; Steinsheim,Gunn; Malmedal,Wenche (Journal of Multidisciplinary Healthcare, 2021)
Aud Moe,1 Rigmor Einang Alnes,2 Bente Nordtug,3 Kari Blindheim,1,2 Gunn Steinsheim,4,5 Wenche Malmedal1,4 1Centre of Care Research Central Norway, Faculty of Health Science, Nord University, Bodø, Norway; 2Department of Health Sciences Ålesund, Norwegian University of Science and Technology (NTNU), Ålesund, Norway; 3Faculty of Health Science, Nord University, Bodø, Norway; 4Department of Public Health and Nursing, Norwegian University of Science and Technology (NTNU), Trondheim, Norway; 5Centre for Development of Institutional and Home Care Services, Åfjord, NorwayCorrespondence: Aud MoeCentre of Care Research, Faculty of Nursing and Health Science, Nord University, Postbox 1490, Bodø, N-8049, NorwayTel +47 911 31 163Email aud.moe@nord.noAim: This study aimed to gain insight into factors that influence everyday coping strategies as described by persons with early to intermediate dementia.Background: Living with dementia presents difficulties coping with everyday life. This study focuses on coping with everyday life for persons with mild to moderate dementia in order to facilitate their ability to live at home.Design: A qualitative study.Methods: Individual interviews with 12 persons with dementia were conducted in their own homes.Findings: Coping with everyday life can be influenced by the experience of the diagnostic process and by information about dementia. It can also be affected by stigmatization of persons with dementia, as well as by challenges in everyday life. In addition, challenges in receiving help may include poor continuity of services and healthcare staff with limited competence. By contrast, person-centered care led to positive experiences that supported everyday coping skills. Most of the respondents wanted to participate in day care several days a week. Other positive experiences were making new friends and participating in meaningful activities; such experiences could enhance to coping strategies.Conclusion: To strengthen everyday coping for persons with dementia living at home, there is a ...